1. ## function notation

1. Determine the following where f(x) = 2x2 - x + 3
a. f(-4)
b. f(0)
c. f(7)
d. f(2y)

2. Originally Posted by euclid2
1. Determine the following where f(x) = 2x2 - x + 3
a. f(-4)
b. f(0)
c. f(7)
d. f(2y)
Just substitute each value of x into f(x)

a) $\displaystyle f(-4)=2(-4)^2-(-4)+3$ and simplify.

Do same for the others.

3. so its f(-4)=39, right?

4. Yes.

5. ## notation

Is f(x)=(2x)2-x+3 or
(2)(2)-x+3?

6. From what he wrote, it seems to be $\displaystyle f(x) = 2x^2 -x+3$

7. ## text

Ah. I see. So would the solution to f(2y) be quadratic? P.S. How do you guys type in that font(where 2x^2 actually looks like 2x^2)?

8. Originally Posted by EyesForEars
Ah. I see. So would the solution to f(2y) be quadratic?
$\displaystyle f(x)=2x^2-x+3$

$\displaystyle f(2y)=2(2y)^2-(2y)+3$

$\displaystyle f(2y)=8y^2-2y+3$

Originally Posted by EyesForEars
P.S. How do you guys type in that font(where 2x^2 actually looks like 2x^2)?
It's called Latex (pronounced Lay-tek), and you can go here and look at the first post for a tutorial.

You can also click on the equation or whatever in the post and you can see the code used to form it.